2021
DOI: 10.1016/j.jtct.2021.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of the BNT162b2 mRNA COVID-19 Vaccine in Patients after Allogeneic HCT or CD19-based CART therapy—A Single-Center Prospective Cohort Study

Abstract: Data are scarce regarding both safety and immunogenicity of the BNT162b2 mRNA COVID-19 vaccine in patients undergoing immune cell therapy, thus we prospectively evaluated these 2 domains in patients receiving this vaccine after allogeneic HCT (n=66) or after CD19-based CART therapy (n=14). Overall, vaccine was well tolerated, with mild non-hematologic vaccine-reported adverse events in minority of the patients. 12% (after first dose) and 10% (after second dose) of the patients developed cytopenia and there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
184
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(214 citation statements)
references
References 20 publications
18
184
0
2
Order By: Relevance
“…This is in agreement with findings reported by Greenberg et al (21) in a non-transplant hematologic malignancies cohort, indicating a lower response to the vaccine among patients treated with B cells directed therapies. Additionally, In a cohort of 80 patients post cellular therapies, Ram et al (16) observed an association between higher CD19 levels and humoral response to the vaccine, while a higher CD4 + /CD8 + ratio was associated with a cellular response. In another recent publication evaluating patients post cellular therapies, Dhakal et al (22) reported on a cohort of 130 patients and did not find a statistically significant association between immune recovery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is in agreement with findings reported by Greenberg et al (21) in a non-transplant hematologic malignancies cohort, indicating a lower response to the vaccine among patients treated with B cells directed therapies. Additionally, In a cohort of 80 patients post cellular therapies, Ram et al (16) observed an association between higher CD19 levels and humoral response to the vaccine, while a higher CD4 + /CD8 + ratio was associated with a cellular response. In another recent publication evaluating patients post cellular therapies, Dhakal et al (22) reported on a cohort of 130 patients and did not find a statistically significant association between immune recovery.…”
Section: Discussionmentioning
confidence: 97%
“…However, among patients with malignancies (10,11) and recipients of solid organ transplantation (12)(13)(14) emerging data suggest lower vaccine efficacy compared to the healthy population. Data for patients undergoing cellular therapies are sparse, with small studies reporting attenuated humoral and/or cellular immune responses (15)(16)(17). We therefore aimed to assess immune responses to mRNA COVID-19 vaccines among patients who underwent cellular therapies at our center, with the goal of identifying predictors of response, determining the ideal timing for vaccination, and to identify patients at high risk for non-protective immune responses who might benefit from additional doses ('boosters') of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The latter group consisted of the 45% of HSCT patients who were no longer on immunosuppressive treatment. A recent study on 66 patients after allogeneic HSCT found evidence of a humoral and/or cellular response to the vaccine in 75% [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In a comparably designed study including allogeneic HCT recipients receiving a 2-dose mRNA SARS-CoV-2 vaccine regimen and tested with the same serologic assay, seroconversion was observed in 75% of 57 tested participants, with median titers of 178 AU/mL. 3 SARS-CoV-2-specific T-cell responses were documented by enzyme-linked immune absorbent spot assay in 19% of 37 tested individuals, all of whom also seroconverted. As in the current study, the majority of participants were also more than 12 months post-HCT, and seroconversion was positively associated with longer duration since HCT.…”
mentioning
confidence: 97%